A contrast-enhanced ultrasound-based nomogram for the prediction of therapeutic efficiency of anti-PD-1 plus anti-VEGF agents in advanced hepatocellular carcinoma patients - Sun, Chao; Wang, Qian; Hou, Lu; Zhang, Rui; Chen, Yu; Niu, Lijuan (Frontiers in Immunology, 2023)
Background: There is no study focusing on noninvasive predictors for the efficacy of sintilimab (anti-PD-1) plus IBI305 (a bevacizumab biosimilar) treatment in advanced hepatocellular carcinoma (HCC).: A total of 33 patients with advanced HCC were prospectively enrolled and received sintilimab plus IBI305 treatment from November 2018 to October 2019. Baseline characteristics including clinical data, laboratory data and tumor features based on pretreatment CT/MR were collected. Meanwhile, pretreatment contrast-enhanced ultrasound (CEUS) for target tumor was performed and quantitative parameters derived from time intensity curves (TICs). A nomogram was developed based on the variables identified by the univariable and multivariable logistic regression analysis. The discrimination, calibration and clinical utility of the nomogram were evaluated. Results: Tumor embolus and grad ratio were significant variables related to the efficacy of sintilimab plus IBI305 strategy. The nomogram based on these two variables achieved an excellent predictive performance with an area under curve (AUC) of 0.909 (95% CI, 0.813-1). A bootstrapping for 500 repetitions was performed to validate this model and the AUC of the bootstrap model was 0.91(95% CI, 0.8-0.98). The calibration curve and decision curve analysis (DCA) showed that the nomogram had a good consistency and clinical utility. Conclusions: This study has established and validated a nomogram by incorporating the quantitative parameter of pretreatment CEUS and baseline clinical characteristic to predict the anti-PD-1 plus anti-VEGF treatment efficacy in advance HCC patients.